WEB 2.0 AND THE ITS INFLUENCE IN THE TOURISM SECTOR - Elton Noti (European Scientific Journal, ESJ, 2013)
The widespread use of the Internet for information search about travel and tourism, but especially different applications associated with Web 2.0 technologies such as social networks (facebook, twitter, my space) podcasting, RSS etc, has made many people who travel for tourism purposes to take information and interact with tourism service providers at any time, without paying high costs, in different forms as well, from writing in chat to audio-visual elements associated with tourism demand and supply.The main objective of this paper is to study whether the use of Web 2.0 is an efficient and useful method for the implementation of tourism marketing and to evaluate direct impacts that Web 2.0 has on costumer’s decisions.Also, this paper presents the impact of Web 2.0 tools, both from the tourism supply and demand point of view, considering that more and more people are using it for tourism purposes.